KEEFEKTIFAN LAYANAN INFORMASI BERBANTUAN MEDIA FILM PENDEK DALAM MEREDUKSI GAYA HIDUP HEDONISME PADA MAHASISWA - Putri Oktaria, Dwi; Rasmanah, Manah; Janare Putra, Bela (CONS-IEDU: Jurnal Program Studi Bimbingan Dan Konseling Islam, 2024)
To find out the hedonistic lifestyle of students before being given information services assisted by short film media, secondly to find out how the implementation of information services assisted by short film media in reducing hedonistic lifestyles in students, and thirdly to find out how effective the information service assisted by short film media is in reducing the hedonistic lifestyle of students. hedonistic life among students in the Islamic counseling study program. The type of research used was quantitative with experimental methods, while the design used in this research was one group pretest-posttest using a sample of 59 people, and was selected again using a purposive sampling technique with a total of 8 students who were given treatment. Data collection techniques use Likert scale questionnaires and documentation. Meanwhile, data analysis used the Wilcoxon test. The results of the study showed that the level of students' hedonistic lifestyle before being given treatment was in the high category with an average value (M) = 80.375, and after being given treatment was in the low category with M = 43.625. Wilcoxon test analysis produced a score of Z = -2.524 which shows that information services assisted by short film media are effective in reducing hedonistic lifestyles in students of the Islamic Counseling Guidance study program at UIN Raden Fatah Palembang